Improved brain perfusion after electrical cardioversion of atrial fibrillation - Gardarsdottir, Marianna; Sigurdsson, Sigurdur; Aspelund, Thor; Gardarsdottir, Valdis Anna; Forsberg, Lars; Gudnason, Vilmundur; Arnar, David O (Europace (London, England), 2020)
Abstract Aims Atrial fibrillation (AF) has been associated with reduced brain volume, cognitive impairment, and reduced cerebral blood flow. The causes of reduced cerebral blood flow in AF are unknown, but no reduction was seen in individuals without the arrhythmia in a previous study. The aim of this study was to test the hypothesis that brain perfusion, measured with magnetic resonance imaging (MRI), improves after cardioversion of AF to sinus rhythm (SR). Methods and results All patients undergoing elective cardioversion at our institution were invited to participate. A total of 44 individuals were included. Magnetic resonance imaging studies were done before and after cardioversion with both brain perfusion and cerebral blood flow measurements. However, 17 did not complete the second MRI as they had a recurrence of AF during the observation period (recurrent AF group), leaving 17 in the SR group and 10 in the AF group to complete both measurements. Brain perfusion increased after cardioversion to SR by 4.9 mL/100 g/min in the whole brain (P < 0.001) and by 5.6 mL/100 g/min in grey matter (P < 0.001). Cerebral blood flow increased by 58.6 mL/min (P < 0.05). Both brain perfusion and cerebral blood flow remained unchanged when cardioversion was unsuccessful. Conclusion In this study of individuals undergoing elective cardioversion for AF, restoration, and maintenance of SR for at least 10 weeks after was associated with an improvement of brain perfusion and cerebral blood flow measured by both arterial spin labelling and phase contrast MRI. In those individuals where cardioversion was unsuccessful, there was no change in perfusion or blood flow.